The Role of the ICE Model in Doctor-Patient Shared Decision Making - Li, Katherine Ning (JURNAL KESMAS DAN GIZI (JKG), 2024)
The ICE model plays a crucial role in shared decision-making between patients and healthcare providers. Adequate information helps patients better understand their health conditions and make informed choices; effective communication facilitates building mutual trust and reaching consensus between providers and patients; and the demonstration of empathy can alleviate patients' anxiety and enhance their confidence in participating in decision-making. In recent years, the application of the ICE model in clinical practice has gained increasing attention. This article mainly explores and analyzes the application of the ICE model in medical practice and its impact on the quality of patient-provider interactions. The research aims to evaluate how the ICE model promotes effective bidirectional communication between patients and providers, and how providers' empathy can enhance psychological support for patients and treatment adherence. Through this study, the goal is to comprehensively understand the role of the ICE model in improving the quality of healthcare services, strengthening patient-provider relationships, and assisting providers in delivering more personalized, patient-centered care. Finally, current challenges are discussed, and future development directions are proposed.